Diabetes Antibody Standardization Program: First evaluation of assays for autoantibodies to IA-2β - Schlosser, Michael (American Diabetes Association, 2011)
OBJECTIVE: Autoantibodies to IA-2β (IA-2βA) are important risk markers of type 1 diabetes. We report the first Diabetes Antibody Standardization Program (DASP) evaluation of IA-2βA assays. RESEARCH DESIGN AND METHODS: Thirteen laboratories from nine countries received coded sera from 50 patients with newly diagnosed type 1 diabetes and 100 healthy blood donors. IA-2βA results were analyzed using receiver operating characteristic (ROC) curves. Concordance of antibody levels was compared using counts per minute (cpm), local and standard curve–derived common units. RESULTS: Median laboratory-assigned sensitivity was 47% (interquartile range [IQR] 45–51), specificity 98% (IQR 95–99), adjusted sensitivity at 95% specificity 50% (IQR 49–53), and area under the ROC curve 0.70 (IQR 0.69–0.73). Use of common IA-2βA units improved concordance between assays compared with local units and cpm (P < 0.0001). CONCLUSIONS: IA-2βA assays in multiple laboratories worldwide achieved good concordance and high specificity for type 1 diabetes. IA-2βA are suitable for inclusion in autoantibody testing for risk assessment in prediabetes.